Comparative approaches to the genetics of human neuropsychiatric disorders - Noh, H (2012)
In this thesis, I investigate the genetics of neuropsychiatric disorders by analysing large data sets derived from high-throughput experiments, using novel comparative genomics approaches. In the first project, I explore characteristics of rare, de novo copy number variants identified among autism patients by employing various bioinformatics resources including Mouse Genome Informatics phenotypes, Gene Ontology terms, and protein-protein interactions. I describe how I objectively identified a number of mouse model phenotypes that are significantly associated with autism, and that provide insight into the aetiologies for both copy number deletions and duplications. In the second project, I investigate the genetics of obsessive-compulsive disorder by resequencing genomic regions of human case-control cohorts and the best spontaneous disease model organisms, namely dogs with canine compulsive disorder, and breed-matched controls. Targeted sequencing experiments yielded a large number of high-quality genetic variants in both humans and dogs. I prioritised variants and genes using case- control comparisons and functional annotations such as types of mutation, evolutionary conservation status and regulatory marks. In turn, I generated several hypotheses that are experimentally tractable. Replication of these findings in a larger cohort is necessary, although it lies beyond the scope of this thesis. Results from both projects indicate that the analytical frameworks employed in this thesis could be profitably applied to other neuropsychiatric disorders.